Violence and the politics of prestige: the fascist turn in colonial Libya. Issue 2 (May 2015) - Ryan, Eileen
Abstract : In 1922–1923, Fascist Party leaders hoped to define a sharp break from previous approaches to colonial rule and imperial expansion in Italy's Libyan territories. Mussolini's nomination of Luigi Federzoni, a leading figure of the Italian Nationalist Association, as the Minister of Colonies at the end of 1922 signalled a new era in Italian colonial administration focused on aggressive expansion and the institution of what was known as a 'politics of prestige'. This definition of a fascist style of colonial rule appealed to the enthusiasm for violence among blackshirt militias and early fascist supporters in the Libyan territories. This definition of a fascist style of colonial rule, however, inspired immediate reaction from both colonial officials, with stakes in maintaining a measure of continuity and stability, and from those within the nascent Fascist Party who wanted to promote an alternative model of fascism in the colonies. This article examines contests to define fascism and fascist colonial rule in the Libyan territories through the employment of voluntary militias, the competing voices of Fascist Party outposts, and various programmes for the development of a colonial culture.